Consumer protection under Islamic law in the service industry - Abu Bakar, Elistina; Amin, Naemah (Institut Sosial Malaysia, 2011)
Consumer protection refers to safeguards against malpractice and exploitative techniques by suppliers of goods or services that adversely affect consumers. The area that seems to be most neglegted is consumer protection in the service industry. However, they are becoming important to consumers and have raised complicated legal issues. Unlike the supply of goods, in which the product quality can be assessed before a sale, a supply of services involves human activity that cannot be subject to such control. Furthermore, consumers often lack technical expertise and are therefore in a weak bargaining position. They are not in a capacity to discuss fully their requirements with service providers and thus can be at the latter's mercy. The aim of this article is to examine the principles under the Islamic law of transactions that give protection to consumers in the service industry. The discussion focuses on the Islamic values and references are made to the opinions of scholars of four schools of thought i.e. Hanafi, Shafi', Hanbali and Maliki. It is submitted that Malaysia should adopt these principles into the legislation and consumer policy so as to strengthen the consumer protection in the country.